2012
DOI: 10.4236/jtts.2012.24031
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability and Transferability of Non-Motorized and Total Trip Generation Models

Abstract: Transportation systems provide a means for moving people and the goods from which they are spatially separated. Of the two means of surface transportation, the motorized mode is used extensively for utilitarian travel in developed countries. The increasing reliance on motorized travel has contributed to increased traffic congestion, air pollution, and greenhouse emissions. Non-motorized travel has recently received significant attention as a means to reduce congestion and environmental problems and improve hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…This finding echoes Cerin and Leslie's (62) work on recreational walk trips but contradicts others (63,64). Mature households are prone to make fewer walk trips, which is consistent with previous studies on the impact of age on walking (38,46,57). Furthermore, daily walk trips decrease with the number of workers in the household, consistent with New et al's ( 54) work based on the 2012 Utah Household Travel Survey.…”
Section: Results and Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…This finding echoes Cerin and Leslie's (62) work on recreational walk trips but contradicts others (63,64). Mature households are prone to make fewer walk trips, which is consistent with previous studies on the impact of age on walking (38,46,57). Furthermore, daily walk trips decrease with the number of workers in the household, consistent with New et al's ( 54) work based on the 2012 Utah Household Travel Survey.…”
Section: Results and Analysissupporting
confidence: 87%
“…This finding is consistent with that of Ewing and Cervero, who found that individuals are more likely to take nonmotorized modes for work trips when either the residential or job location is densely populated (59). As expected, households that own more vehicles tend to make fewer walk trips (57). Higher-income households were estimated to make more walk trips, possibly because higherincome neighborhoods enjoy greater provisions of pedestrian facilities (60,61).…”
Section: Results and Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Thus the pedestrian traffic safety management at TWC intersections deserves a worthwhile re-examination. Further, the recent push to increase non-motorized transportation in the last decade has led to an increased need for research and data relating to walking and walk ability [8,9]. The aim of the study is to design a modified traffic signal phasing at a TWC When not controlled, the intersection operates as a priority intersection with traffic on Obbo and CocaCola roads yielding to traffic on Taiwo and Challenge road approaches.…”
mentioning
confidence: 99%